Analisis Faktor – Faktor Yang Mempengaruhi Jumlah Pembelian Pakaian Bekas di Pasar Gedebage Kota Bandung - Lukman Nul Hakim; Lella N.Q.Irwan (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2021)
This study aims to examine the factors that affect the total purchase of second-hand clothes by consumers in Gedebage Market, Bandung City. Factors examined in this study are price, income, product diversity, and product quality as independent variables. And the total purchase as a dependent variable. The method is an explanatory method. The population in this study are consumers who buy or have bought second-hand clothes in the Gedebage Market, Bandung City. Sampling technique using the technique of Purposive Sampling, the sample in this study amounted to 60 respondents. The results of this study indicate that the part of the variable price, income, and product diversity have a positive and significant effect on the total purchases of second-hand clothes by consumers in the Gedebage market, whereas product quality has no effect significant. The simultan of price, income, product variety, and product quality has a positive and significant effect on the total purchases of second-hand clothes by consumers in the Gedebage market amounted to 62%.